ANALISIS PENGARUH CAR, DANA PIHAK KETIGA (DPK), NIM, dan LDR TERHADAP PROFITABILITAS PERBANKAN DENGAN LDR SEBAGAI VARIABEL INTERVENING - Pardede, Desi Natalia; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2016)
The aim of this research is to identify and analyze the determinants of return on Assets (ROA) in General Banking of Indonesia in the period of 2010 â€“ 2014. ROA is dependent variable in this research, as profitability indicator. There are three independent variables that used, which are Capital Adequacy Ratio (CAR), Third Party Funds (TPF), Net Interest Margin (one year before) (NIMt-1), and an intervening variable which is Loan to Deposit Ratio (LDR). Sampling technique used is purposive sampling with criteria as General Banking in Indonesia who provide annual reports and traded on Indonesia Stock Exchange (IDX) during period 2010 through 2014 and forwarded to Bank Indonesia. Obtained by amount sampel as much 28 companies from 42 banking company in Indonesia 2010-2014Â period. Analyzed with Path Analysis technique. The data is analyzed using SPSS 20 program.The result of this study proving that TPF and NIMt_1 have positive relationship and statistically significant toward LDR. CAR has negative relationship and insignificant toward LDR. CAR and LDR have positive and significant relationship toward ROA. TPF Â has positive relationship and insignificant toward ROA. NIMt_1 has negative relationship and significant toward ROA. Then, TPF and NIMt_1 has significant relationship toward ROA mediated by LDR as intervening variable.